Neuropsychological functioning in children and adolescents with pharmacoresistant epilepsy due to malformations of cortical development. - Arenivas, Ana; Ferguson, Lisa; Lapin, Brittany; Li, Yadi; Blumcke, Ingmar; Najm, Imad; Busch, Robyn M. (Epilepsy and Behavior, 2025)
PURPOSE: Almost half of pharmacoresistant epilepsies in childhood and adolescence are caused by malformations of cortical development (MCDs), but little is known about the associated neuropsychological morbidities. This study comprehensively characterized presurgical neuropsychological functions in children and adolescents with pharmacoresistant epilepsy due to MCDs and examined their relationships to neuropathological substrate and other clinical variables. METHODS: Retrospective data were obtained from 137 children and adolescents (mean age = 13 years; 58 % male) who underwent resective surgery for treatment of epilepsy and had pathologically-confirmed MCDs. Neuropsychological domain composite scores and overall cognitive phenotype were examined. Logistic regressions identified demographic and disease variables associated with neuropsychological functioning. RESULTS: Pathological diagnoses included focal cortical dysplasia (FCD, n = 69; 30 % FCD Type IIB, 20 % FCD Type IIA, 1 % FCD Type IA) and other MCDs (n = 68; 23 % mild MCD, 7 % polymicrogyria, 7 % tuberous sclerosis complex, 6 % complex MCD, 5 % mild MCD with oligodendroglial hyperplasia in epilepsy, 2 % periventricular nodular heterotopia). Performance was highly variable, ranging from superior to extremely low across cognitive domains. Impairment rates ranged from 40.1 % (visuospatial skills) to 70.8 % (fine motor skills). Of patients and parents/caregivers able to complete standardized inventories of mood and anxiety, approximately 20 % endorsed concerns for depression and anxiety. A large subset (29 %) demonstrated cognitive deficits limited to a single domain, with processing speed (24 %) and language (20 %) being the most commonly affected domains. Younger age at epilepsy onset and multilobar seizure locus were associated with lower cognitive performance across multiple domains. No significant differences in cognition existed between children and adolescents with focal cortical dysplasias and those with other MCDs. CONCLUSIONS: Findings suggest the range of cognitive abilities in children and adolescents with MCDs is much broader than previously described, with over 20% demonstrating an intact cognitive phenotype. Despite high prevalence of cognitive impairment in this cohort, significant variability existed at the individual level that was not fully accounted for by demographic and clinical variables. Results highlight the importance of neuropsychological evaluation and routine emotional/behavioral screening in pediatric epilepsy caused by MCDs.
EVALuna2:592286